A Criminological Review of Online Fraud Crimes - Rafiqi Amran, Mohammad Fauzan; Asriati, Asriati; Arifin, Muhammad Ya'rif (HORIZON PUBLIC LEGAL STUDIES, 2025)
This research aims to find out and analyze the factors that cause online fraud crimes and to find out and analyze the efforts made by the authorities in dealing with online fraud crimes. This research uses empirical research methods, the types of data used are primary and secondary data, primary data is obtained directly at the research location by means of direct interviews related to the problem being researched with parties who are directly involved with the problem being discussed to obtain research data. Meanwhile, secondary data is obtained from literature such as documents, written sources such as journals, books, legislation and so on which are related to the problem being studied. The results of this research show that the factors that cause online-based fraud crimes are economic factors, environmental factors, socio-cultural factors and intellectual factors. Efforts made by the authorities in overcoming online-based fraud crimes include preventive efforts, repressive efforts, and implementation of the Information and Electronic Transactions Law against cyber crimes. The preventive efforts carried out include providing advice to the public through electronic media and related cyber crimes to be forwarded to the wider community. Repressive efforts include processing every cyber crime case that is handled in accordance with applicable regulations. The research recommends to the police as law enforcement officers that they should not only carry out outreach, but also block sites that are suspected to contain elements of crime and it is hoped that in the future the police will increase supervision over the use of social media by optimizing POLRI PRECISION.